Adaptive employment reform and inclusive skill transition action (AERISTA): The concept of collaborative labor law reform in response to automation - Muhammad Rafli Mawla Rakhman; Charles Leonard Moniaga (Green Governance: Exploring Politics, Social Justice, and the Environment, 2025)
Background: The Indonesian Constitution and labor laws guarantee the right to work and a decent livelihood, yet these provisions face serious challenges in the Society 5.0 era where artificial intelligence, automation, and other digital technologies disrupt labor markets at a scale that outpaces legal adaptation. Previous studies have identified fragmented regulations concerning termination of employment, limited training mechanisms, and the absence of fiscal instruments to address automation’s social impact, but legal protections remain inadequate and reactive. This study aims to analyze the weaknesses of Indonesian labor law in mitigating automation-driven layoffs and to propose a comprehensive reform framework. Methods: Using normative legal research with statute, case, and conceptual approaches, supported by primary legal sources (such as the Constitution and Employment Law), secondary sources (expert analyses and journals), and tertiary materials (dictionaries and encyclopedias), data were collected through bibliographic studies and analyzed qualitatively through grammatical, systematic, and comparative interpretations. Findings: The findings show that Indonesian labor law is ill-prepared to anticipate mass layoffs, competency mismatches, and discrimination risks from AI-based recruitment, necessitating a holistic reform model. Conclusion: As a response, this study introduces, a four-pillar framework that integrates the strengthening of labor policies to provide legal certainty, National Talent Mapping (an AI-based system to profile and align workforce competencies with industry needs), Mandatory Reskilling programs to equip workers with adaptive and competitive skills, and a Targeted Automation Tax as a fiscal mechanism to control automation adoption and fund social protection for affected workers. Novelty/originality of this article: AERISTA thus positions workers not as passive victims of disruption but as active participants in labor transformation, ensuring inclusivity, social justice, and sustainability in employment law.